Rompimento e delimitação da área de inundação da barragem Salto Moraes em Ituiutaba/MG - Mota, Kevin Reiny Rocha (2017)
This study aims to simulate a hydraulic hypothetical rupture of the Salto Moraes dam on the Tijuco Rio by overtopping and through graphic results such as streamflow-hydrographs downstream of the dam and flood maps to analyze the impact caused in the vicinity of the downstream channel of the dam. The main objective of the study is to analyze the calibration of the coefficient CN in each sub - basin upstream of the Salto Moraes dam, to investigate the influence of the parameters defining the rupture gap formation on the streamflow hydrograph immediately downstream of the dam, to investigate the influence of the empirical equations of gap formation parameters on the streamflow hydrograph immediately downstream of the dam and to identify the risk level that dam rupture causes to human density and buildings close to the canal downstream of the dam. The Salto Moraes Dam in Ituiutaba-MG was chosen as the object of study as a result of the presence of buildings, treatment plants and human density in the vicinity of the downstream channel, and how the hypothetical rupture of the dam can impact human lives, buildings and the water supply to the city. In the methodology, the downstream channel of the Salto Moraes dam with the use of Hec-GeoRas was object of study, the streamflow hydrographic basin upstream of the dam was studied in order to determine the streamflow hydrograph that flows into the dam, and for this it was necessary to identify all the sub-basins and produce the study of land use and planning, calculate the mean precipitation at a specific date by applying the Thiessen method and with the use of Hec-Hms, calibrate the coefficient CN so that the maximum flow in the dam is equivalent to the flow of the indicated fluviometric station. With the calibrated CN and the highest precipitation of the basin of the last 50 years, three Hec-Hms simulations were performed to determine the instream flow that hypothetically, would break the dam. In addition, the Hec-Ras methodology was used to simulate the rupture in a non-permanent structure. In the Hec-Ras simulations, 14 scenarios were created to investigate the influence of breach-forming parameters on the streamflow hydrograph immediately downstream of the dam. An assessment was made on the influence of four empirical equations arranged in the Hec-Ras on the peak flow of the streamflow hydrograph immediately downstream of the dam. With the equation that generated the highest peak flow, a flood map and the parameters available in research, the flooded area caused by the rupture of the dam was analyzed. After the methodology, the results were presented. In the downstream channel of the dam, 277 cross sections of 50 km in length was created. In the catchment area of the dam, 4 sub-basins were identified and 12 fictitious sub-basins were created to take into account the high diffuse contribution in the Tijuco River. The land use planning was done considering 4 classes and it was identified that the basin has greater pasture occupation. In addition, by analyzing soil maps of the region it was identified that the soil is Dystrophic Red Latosol, which is framed in the group of soil A. The Hec-Hms simulations generated a maximum flow of 1227 m³ / s in the Salto Moraes dam. In the Hec-Ras, the simulations demonstrated that with an increase in height of the gap, the flow decreases, with an increase in the width of the gap the peak flow increases, with an increase of the lateral slope of the gap the peak flow decreases and that the progression of the sine wave generates a higher peak flow than the linear progression. The simulations comparing the four empirical equations showed that the equation of "Xu and Chang (2009)" generated a higher peak flow. A map of the flooded area was devised and it was verified that the rupture of the dam impacts the outskirts of the city of Ituiutaba-MG.